PREVENTION AND PREDICTION IN DIABETES MELLITUS TYPE 2 - Martín Rodríguez (Revista de la Sociedad Argentina de Diabetes, 2020)
First-degree relatives of people with type 2 diabetes mellitus (T2DM) are at higher risk of developing this condition since offspring and siblings have a risk three times greater than that of the general population. This increased risk has genetic and environmental components. The latter likely come from shared risk factors, such as sedentary lifestyle, physical inactivity, and obesity.